Recent Advances in Electrophilic Amination Reactions - Corpet, Martin; Gosmini, Corinne (Synthesis, 2014)
Electrophilic nitrogen sources are an increasingly popular class of reagents for the formation of C–N bonds. Recently, a significant number of useful methodologies have been reported, in particular, examples using transition-metal catalysis. This review summarizes the latest developments in this field, with a focus on very recent advances.1 Introduction2 Reactions with Stoichiometric Organometallic Reagents2.1 Organoboron Nucleophiles2.2 Zirconium Derivatives2.3 Silicon Derivatives2.4 Grignard Reagents2.5 Organozinc Reagents3 Catalytic Organometallic Species3.1 C–H Activation Reactions3.2 Heterocycle Synthesis via Addition/Amination Sequences3.3 Narasaka–Heck (or Amino-Heck) Reactions4 Enolates as Nucleophiles5 Conclusion
Keywords: amination; catalysis; heterocycles; C–H activation; organometallic reagents